Joint association of serum sodium and frailty with mild cognitive impairment among hospitalized older adults with chronic diseases: a cross-sectional study - Hui, Zhaozhao; Wang, Lina; Deng, Jing; Liu, Feng; Cheng, Liping; Li, Yajing; Tian, Yuxin; Ma, Le; Liu, Xiaohong (Frontiers in Nutrition, 2024)
Background: To examine the associations of serum sodium and frailty with the risk of mild cognitive impairment (MCI) among hospitalized older adults with chronic diseases.A cross-sectional study was conducted in 403 hospitalized older adults with chronic diseases. Serum sodium concentration was assessed by the ion-selective electrode method, frailty status was evaluated by the FRAIL scale, and MCI was determined by the Montreal Cognitive Assessment (MoCA). Multiple logistic regression models were used to estimate the associations of serum sodium and frailty with MCI.Results: Participants with the lowest tertile of serum sodium had a higher risk of MCI than those in the middle tertile group (OR=1.75, 95% CI: 1.01-3.04). Below 143 mmol/L, the risk of MCI was 1.38 (95% CI: 1.03-1.84) for per 1 SD decrease in serum sodium. Compared with the robust group, frailty was significantly associated with an increased risk of MCI (OR=3.94, 95% CI: 1.92-8.10). Moreover, in comparison with participants with the middle tertile of serum sodium and who were robust/prefrail, those with frailty and either the lowest (OR=5.53, 95% CI: 2.08-14.67) or the highest tertile of serum sodium (OR=3.48, 95% CI: 1.20-10.05) had higher risks of MCI.Both lower and higher serum sodium impose a significantly higher risk for MCI in older adults with frailty. This could inform the design of clinical trials and the development of guidelines and recommendations for correcting serum sodium and frailty in hospitalized older adults with chronic diseases.